2020
DOI: 10.1371/journal.pone.0238910
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation in inflammatory bowel disease patients: A systematic review and meta-analysis

Abstract: Objectives Current evidence on fecal microbiota transplantation for inflammatory bowel disease is inconclusive. We conducted a systematic review to gather evidence on the efficacy and safety of fecal microbiota transplantation for inflammatory bowel disease. Methods Systematic searches were conducted in PubMed, Scopus, and Web of Science. Clinical remission was considered as the primary endpoint. Pairwise meta-analyses were performed for the randomized controlled studies (Mantel Haenszel, random effects model)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 73 publications
2
50
1
1
Order By: Relevance
“… Appeared changed at two weeks (only data point). Not described Bajaj et al, 2017 32 and long term data reported in Bajaj et al, 2019 56 Yes Yes Changes appeared to persist for over one year (reported in long term paper). Not described Bajaj et al, 2019 33 Yes Not measured Appeared changed at day 30 (only data point).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… Appeared changed at two weeks (only data point). Not described Bajaj et al, 2017 32 and long term data reported in Bajaj et al, 2019 56 Yes Yes Changes appeared to persist for over one year (reported in long term paper). Not described Bajaj et al, 2019 33 Yes Not measured Appeared changed at day 30 (only data point).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst other reviews have been conducted with respect to safety of FMT for indications other than CDI, these reviews are either not recent, 65 or were restricted to a single indication such as IBS [29][30][31] and IBD. [32][33][34] With respect to efficacy, whilst other reviews have been published for single indications, such as IBS [29][30][31] and IBD, [32][33][34] there have been no holistic reviews looking at all indications other than CDI. As far as the authors of this review are aware, this review also represents the most up to date systematic review and metaanalysis of the safety and efficacy of FMT for IBS.…”
Section: Strengths and Weaknesses Of The Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Имеющиеся данные об эффективности ТФМ в терапии СРК неоднозначны и противоречивы. В отдельных исследованиях имеются сообщения о возможных благоприятных эффектах данной стратегии лечения, улучшении клинической картины заболевания [71]. Между тем в ряде систематических обзоров сообщается об отсутствии убедительных доказательств эффективности ТФМ при СРК [72][73][74].…”
Section: трансплантация фекальной микробиотыunclassified